Diarrhoeae in thyroid medullary carcinoma: role of prostaglandins and therapeutic effect of nutmeg. Issue 5974 (5th July 1975) - Barrowman, J A; Bennett, A; Hillenbrand, P; Rolles, K; Pollock, D J; Wright, J T
Abstract : In a patient with medullary carcinoma of the thyroid with pulmonary metastases who presented with diarrhoea and steatorrhoea large amounts of prostaglandin-like material were present in peripheral blood, and some was extracted from the tumour. The diarrhoea which persisted after thyroidectomy responded to treatment with nutmeg.